Effect of weight percentage of silicon carbide (SiC) reinforcement particles on mechanical behavior of aluminum metal matrix composite (Al MMC) - Engku Amalina Syazana, Ku Mohd Nazri (2008)
Silicon carbide particle reinforced aluminum matrix composites have been developed over past few decades, owing to their excellent properties like light weight, high elastic modulus and wear resistance. Thus, the silicon carbide particle reinforced aluminum matrix composites are expected to have many applications in aerospace, aircraft, automobile and electronic industries. In this study, aluminum metal matrix composites containing several weight percentages of reinforcement particles were prepared by using powder metallurgy method. The main steps in powder metallurgy are blending, compacting and sintering. The experiments were performed on different composition of silicon carbide powder in the composite. The study presents the results of experimental investigation on mechanical behavior of silicon carbide particle reinforced aluminum matrix. The influence of reinforced ratio of 0, 5, 10 and 15 weight percentage of silicon carbide particles on mechanical behavior was examined. The effect of different weight percentage of silicon carbide in composite on hardness and microstructure was studied. Digital image analyzer was used to characterize the composites. The effect of weight percentage of silicon carbide on hardness of composites was investigated by using Vickers hardness Test. It was observed that the distribution of silicon carbide particles was uniform. The hardness of the composites increased with increasing reinforcement element addition in it. In addition, and for the purpose of verification of the present theory, other published work was also compared and found to be in very good correlation with the predicted result.